2013
DOI: 10.1007/s00198-013-2485-4
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of osteocalcin and procollagen type I N-propeptide plasma levels in a healthy Central European population aged 0–18 years

Abstract: This study provides reference data for OC and PINP in healthy Caucasian children from a Central European population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 28 publications
20
43
0
1
Order By: Relevance
“…This observation is consistent with the known favorable effect of OC on insulin secretion and sensitivity, which are both impaired in T2D, while only the former is abnormal in most cases of T1D. The differences between males and females may be related to sex hormone levels, which have been reported to influence OC metabolism in healthy children and adults …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This observation is consistent with the known favorable effect of OC on insulin secretion and sensitivity, which are both impaired in T2D, while only the former is abnormal in most cases of T1D. The differences between males and females may be related to sex hormone levels, which have been reported to influence OC metabolism in healthy children and adults …”
Section: Discussionsupporting
confidence: 89%
“…The differences between males and females may be related to sex hormone levels, which have been reported to influence OC metabolism in healthy children and adults. [30][31][32][33] Several clinical reports have shown that higher total OC levels are associated with better glucose homeostasis. 5,[8][9][10][11][12] Pediatric studies have been conflicting, with some reports that serum OC is inversely associated with the presence of established T2D and inversely correlated with HbA1c 13 while others found an inverse association between total OC and HbA1c as well glucose parameters in adults but not in children.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed a decline in terms of age at concentrations of formation markers (PINP; OC) and bone resorption (β‐CTX). These results are similar to studies carried out in humans, where concentrations of PINP , β‐CTX , and OC were measured in rhesus monkeys . These age‐related changes in markers most likely were observed due to the physiological evolution between the end of the process of growth and the bone remodeling that occurs with the development of adults .…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Schnitzler & Mesquista () found that drifting osteons with large active canals accounted for over 70% of childhood cortical porosity in biopsies of the iliac crest. The inverse correlation between Po.Dn and age likely reflects a decrease in the remodeling rate after infancy (Szulc et al ; Bayer, ). Ct.Po appears to demonstrate a non‐linear relationship with age.…”
Section: Discussionmentioning
confidence: 99%